Digital processing of video information of objects by the method of contour-structured lines - Vinogradov A.S.; Nasirov A. A.; Tashmanov E.B. (Research Parks Publishers, 2021)
This article describes the developed video compression codec based on the application of the contour-structured lines method, and also presents the results of experiments to identify its practical advantages in digital processing. To assess the reliability of the research results, frames of video sequences of various plots and genres with different redundancy, texture, and mobility of video objects were tested. In this case, both a visual assessment of the image quality and objective metrics of the standard deviation and the peak signal-to-noise ratio (PSNR) were used. The proposed complex use of the methods of contour-structured lines and algorithms for segmentation of image processing and the allocation of contours in a monochrome image makes it possible to improve methods of encoding a video stream and compressing video information, which is expressed in an increase in the efficiency of video information transmission, an increase in channel capacity due to the use of hardware and software modules of processing transmission devices data, compression of the video stream, codecs, and improvement of the video surveillance system of various objects.